Effects of phytogenic additives on meat quality traits in broiler chickens - Orlowski, Sara (J Anim Sci, 2018)
Phytogenics have been reported to improve growth performances in farm animals and are thereby considered as potential key solutions for antibiotic-free livestock nutrition. Yet, their effects on meat quality are still not well defined; therefore, the aim of this study was to determine the effects of 5 experimental phytogenic additives (3 dietary and 2 water supplements) on growth and meat quality in broilers. One-day-old broiler chicks (n = 576) were assigned to 48 floor pens and divided into 6 treatments (Control, AV/HGP/16 premix [AVHGP], Superliv concentrate premix [SCP], bacteriostatic herbal growth promotor [BHGP], AV/SSL/12 [AVSSL], and Superliv Gold [SG]) in a complete randomized design (8 pens/treatment with 12 birds/pen, and 96 birds/group). Feed intake and BW were recorded, and birds were processed at 42 d to evaluate carcass traits. Breast muscle tissues were excised to determine stress- and antioxidant-related genes expression. Both AVSSL- and SG-treated broilers produced heavier (P < 0.05) slaughter weights compared with the control-fed broilers, whereas AVSSL supplementation decreased (P < 0.05) fat pad size and increased (P < 0.05) breast weights compared with the control-fed broilers. Although pH and a* values remained unchanged, L* was decreased (P < 0.05) in all treatment and b* was reduced (P < 0.05) in SG when compared with controls. The trained sensory panelists detected more (P < 0.05) green herb flavor in the breast meat from AVHGP than SCP, SG, and control birds. The expression of superoxide dismutase 2, extracellular signal-regulated kinase 1/2, and JNK gene was upregulated in AVHGP and BHGP compared with the control (P < 0.05). Together, these results indicated that phytogenic additives might improve meat quality of broilers through modulation of stress- and antioxidant-related pathways.